Anterior Chamber Angle Evaluation with Fourier-Domain Optical Coherence Tomography - Matthew Bald; Yan Li; David Huang (Journal of Ophthalmology)
New advances in anterior segment optical coherence tomography (OCT) technology development allow visualizing the anterior chamber angle of the eye with high speed and high resolution. Fourier-domain (FD) OCT instruments working at 840 nm can reliably identify fine angle structures such as the Schwalbe's line. This paper demonstrates quantitative angle assessment with 840 nm FD-OCT and provides diagnostic cutoff values for occludable angle detection. This is useful for angle closure glaucoma diagnosis and management. Moreover, 840 nm FD-OCT is a useful tool for postsurgical evaluation in glaucoma patients.